Evaluation of Field Map and Nonlinear Registration Methods for Correction of Susceptibility Artifacts in Diffusion MRI - Wang, Sijia; Peterson, Daniel J.; Gatenby, J. C.; Li, Wenbin; Grabowski, Thomas J.; Madhyastha, Tara M. (Frontiers in Neuroinformatics, 2017)
Correction of echo planar imaging (EPI)-induced distortions (called “unwarping”) improves anatomical fidelity for diffusion magnetic resonance imaging (MRI) and functional imaging investigations. Commonly used unwarping methods require the acquisition of supplementary images during the scanning session. Alternatively, distortions can be corrected by nonlinear registration to a non-EPI acquired structural image. In this study, we compared reliability using two methods of unwarping: 1) nonlinear registration to a structural image using symmetric normalization implemented in Advanced Normalization Tools (ANTs), and 2) unwarping using an acquired field map. We performed this comparison in two different test-retest data sets acquired at differing sites (N=39 and N=32). In both data sets, nonlinear registration provided higher test-retest reliability of the output fractional anisotropy maps than field map-based unwarping, even when accounting for the effect of interpolation on the smoothness of the images. In general, field map-based unwarping was preferable if and only if the field maps were acquired optimally.